Aspirations, Goals, Dreams, and Future Pursuit of Basketball Athletes in the National College Athletics Association (NCAA): A Literature Review - Punzalan, Michelle; Maranan, Mario (JPAIR Multidisciplinary Research, 2024)
This study offers insightful information about academic support programs for student-athletes, highlighting the necessity of all-encompassing assistance and utilizing technology to cater to their requirements. Aspects of academic support included in the evaluation include study halls, writing centers, technology, job transition, counseling, and bridging programs. It emphasizes how crucial customized solutions and a positive team atmosphere are. The necessity of a more comprehensive strategy to affect student-athletes’ conduct, the significance of specialized library education, and the requirement to ease their transition into the workforce are among the study gaps that have been found. To better meet the special needs of student-athletes and pinpoint best practices for various contexts, the abstract suggests that more research be done on the long-term effects of academic support programs, the efficacy of technology-based interventions, and cross-cultural analysis of academic support programs. In addition to offering suggestions for future research to improve academic assistance programs for student-athletes, the abstract contains insightful information about the difficulties and experiences faced by student-athletes.